Mission-Driven Priorities: Public Health in Health Information Exchange - Nangle, Barry (American Medical Informatics Association, 2009)
Developing state- and nationwide health information exchange (HIE) is one of the health priorities defined in the American Recovery and Reinvestment Act. States are expected to take leadership in statewide planning and implementation. To balance limited resources among mandated responsibilities and emerging HIE accountability, we maintain that state public health practitioners must integrate HIE into our mission-driven practice in five priority areas: 1) connecting real-time disease surveillance and notifiable case reporting through HIE to better protect citizens; 2) sharing public health-managed clinical information through HIE for preventive services, 3) conduct health education for targeted populations via HIE to promote healthy lifestyles; 4) leverage public health informatics with Medicaid information system to provide quality healthcare; and 5) serve as a regulator for standardized HIT to participate in healthcare reform. We summarize public health’s broad practice into “Five P’s” and link each domain’s historical foundation, current and proposed practices to sustain success.